Nonunion with Breakage of Gamma Nail and Subsequent Fracture in the Ipsilateral Femur - Takahiro Niikura; Sang Yang Lee; Yoshitada Sakai; Kotaro Nishida; Ryosuke Kuroda; Masahiro Kurosaka (Case Reports in Medicine)
We describe a rare case with breakage of gamma nail accompanied by nonunion of the original fracture and a subsequent new fracture in the ipsilateral femur. A 73-year-old woman suffered a subtrochanteric fracture of the femur, and the fracture was fixed with gamma nail at a previous hospital. However, fracture reduction was not adequately achieved and a large gap remained between the fracture fragments. The fracture demonstrated atrophic nonunion 10 months after surgery, and autologous bone grafting was performed at the same hospital. Two months after the second surgery, a breakage of the nail at the distal screw hole was observed. Twenty-six months after the second surgery, the patient fell and a fracture occurred at the level of the nail breakage. The atrophic nonunion site and fresh fracture site were very close thus demonstrating a segmental fracture. We exchanged the original gamma nail with a long gamma nail and performed autologous bone grafting at the nonunion site. Both the fresh fracture site and the nonunion site obtained bony union. This tragic chain of events was caused by inappropriate initial treatment and replacing the nail to a longer nail and autologous bone grafting were effective as salvage surgery.